Social Enterprises in Albania: Analysis of Albanian Legislation over the Years - Kadrimi, Leonard; Gjeta, Arber (Richtmann Publishing, 2019)
Pursuant to Law no. 65/2016 â€œOn social enterprises in the Republic of Albaniaâ€, the Albanian lawmakers have aimed to regulate the exercise of the profitable activities of non-profit organizations by providing a legal solution and improving the regulatory framework of the so-called, in some countries, the third sector (which is not included neither in state-owned nor in private commercial entities). The law hereof aims to regulate the exercise of non-profit commercial activities, by limiting the types of entities allowed to be non-profit organizations, and therefore leaving the trading companies out of scope. Regarding the object of the law, in order to protect and socially include the vulnerable groups, its scope is limited to employment, provision of employment opportunities, provision of goods and services and economic and social integration for the ulnerable groups, therefore it has set some restrictions on the legal notion of social enterprise. Despite the great legislative work and the good will to finally regulate and stimulate an innovative sector such as the social enterprise, in the de iure condito debate it was mentioned that there is still room for improvement in this part of the legislation, which has not given any or has given only a few effects in practice. Therefore, by analyzing the Albanian legislation in the sector, we aim to provide an explanatory description of Law no. 65/2016 but at the same time, de iure condendo, to ask for a better addressing of the problems that have arisen in practice, in the light of the European and foreign legislation, jurisprudence and doctrine in this field.